Legal Standing Paralegal dalam Proses Beracara di Pengadilan Pasca Putusan Mahkamah Agung RI Tentang Uji Materi PERMENKUMHAM RI no. 1 tahun 2018 tentang Paralegal dalam Pemberian Bantuan Hukum - Mustakim Mustakim; Sania Salamah (Departemen Hukum Perdata, 2020)
The fact that the legal aid provision has not reached all the Indonesian citizens forces the Ministry of Law and Human right to establish the ministerial regulation of the Ministry of Law and Human Right No. 1 year 2018 about Paralegal on legal aid provision which is effectively applied on the 26th January 2018 as the implementation of Act No. 16 year 2011 about Legal Aid. The regulation that gives the Paralegals a spacious room to lawyer in the court resulted in pros and cons if it is contrasted to the position of an advocate within the act No. 18 year 2003 about lawyer, legal aid quality, and monitoring on the provision of legal aid. The statement of the problem is how the legal standing of Paralegal in lawyering in the court as what has already been regulated by the regulation of the Ministry of Law and Human Right No. 1 year 2018. This is a normative research with legislation approach and concept approach. The result of this research found out that there are Paralegal regulations that need to be adjusted with the regulation about legal aid provision such as age limit, qualiﬁ ed educational curriculum, and the need of ethical code that ties up the Paralegal joining law aid organization, so the objective of this constitutional nation to admit, to protect, and to guarantee the human right of the citizens about the access to justice and equality before the law as what has been explained in Article 28 D, article 4 point (1) Constitution of Indonesian Republic Year 1945 could be implemented.